(untitled) (International Journal of Engineering and Computer Science, 2016)
In Past few years growth of wireless ad hoc network has increased rapidly .The single greatest issue in a few wireless network is that it’s, well, wireless! The largest reason to possess a wireless network is as a result of it eliminates the requirement for expensive, ugly, and dangerous wires trailing every where your business and home network. This paper proposes a brand new algorithmic rule known as the Similarity Intention Attack (SIA); the algorithmic rule relies on the Attack Analysis (AA) algorithmic policy rules to predict new attacks intentions in wireless intrusion detection system (WIDS) and allotted the probability values for these intentions. The analysis algorithm shows that our planned algorithmic policy based approach provides higher level wireless security.